An investigation into how grade 9 girls participate during practical work in Physical Science lessons : a case study - Munyanyo, Johanna (Rhodes University, Faculty of Education, Department of Education, 2015)
This research report documented in this thesis focused mainly on the participation of grade 9 girls during practical work in the topic of 'Electricity' in Physical Science lessons at Mwatya (pseudonym) Junior Secondary School in Ohangwena region of Namibia. The study was triggered by the lack of participation of girls during practical work. Underpinned by an interpretive paradigm, the study took the form of a qualitative case study and my unit of analysis was girls' participation during practical work on electricity in particular. The perceptions and experiences of girls about practical work in Physical Science were investigated using the administered questionnaires. The participation of girls during practical work was further explored using interviews (semi-structured and focus group interviews) and observations of selected girls. A thematic approach to data analysis was adopted. The qualitative data from the audio and video transcripts were analysed according to the categories developed and themes that emerged from the analysis process. The categories developed for presenting the data are: teaching methods preferred by girls; importance and roles of practical activities; things that girls enjoy during practical activities; problems experienced by girls during practical activities; preference for doing practical work in groups or as an individual task; if practical work given in groups should the sex of learners be considered or not; activities preferred by girls when they are in single sex and in mixed sex groups; factors that enable girls to participate; and factors that prevent girls from participating. The study found that girls' perceptions about practical work affect their participation during practical work in the topic of Electricity. It also revealed different factors that contribute to either good or poor participation of girls, namely, factors such as mixed-sex group-work, limited science prior experience (knowledge), unequal treatment from teachers during lessons and home environment were identified as contributing to poor participation. Girls however suggested some factors that they think could enable them to participate freely and actively during practical work. In view of these findings, this study recommends that teacher training institutions should train teachers to plan practical work in a gender sensitive manner. Schools should be provided with enough materials as sharing materials can contribute to poor participation of girls during practical work especially when they are in mixed groups with boys. There is a need for science teachers to assess the learning taking place during practical work and, finally, textbook suppliers should be monitored in a way that enables the supply of gender sensitive printed materials.
Keywords: Physical sciences -- Study and teaching (Secondary) -- Namibia; Teenage girls -- Education; Sex differences in education -- Namibia; Sex discrimination in education -- Namibia; Physical sciences -- Study and teaching (Secondary) -- Sex differences